HIGHLY EFFICIENT DYE-SENSITIZED SOLAR CELLS BASED ON THE DISCHARGED TiO2 NANOPARTICLES - T. M. Paronyan; A. M. Kechiantz; M. C. Lin
Mesoporous nanocrystalline TiO2 photoelectrodes consisting of discharged nanoparticles have been fabricated. A high conversion efficiency (~9.5 %) was achieved with these photoelectrodes.
Keywords: Physics; Electronic structure and electrical properties of surfaces